"The ultimate risk:" How clinicians assess the value and meaning of genetic data in cardiology. (September 2021) - Owens, Kellie
In modern medicine, health risks are often managed through the collection of health data and subsequent intervention. One of the goals of clinical genetics, for example, is to identify genetic predisposition to disease so that individuals can intervene to prevent potential harms. But recently, some clinicians have suggested that patients should undergo less testing and monitoring in an effort to reduce overdiagnosis and overtreatment. In this paper, I explore how clinicians navigate the tension between identifying real disease risks for their patients with concerns about overdiagnosis and overtreatment. I focus on clinicians ordering genetic testing for inherited cardiovascular diseases. Of the genes determined to be "clinically actionable" by the American College of Medical Genetics and Genomics (ACMG), half are related to cardiovascular diseases. But, due in part to high levels of uncertainty surrounding cardiovascular genetics, there is still disagreement within the field about how to order and interpret these tests. Based on semi-structured, in-depth interviews with 20 clinicians who order genetic testing for cardiovascular diseases, I find that there is considerable variability in the ways that clinicians determine which types of genetic tests are appropriate for their patients and how they interpret test results. Most importantly, I find that many providers do not presume that more genetic data will lead to better care. Instead, increased genetic data can lead to confusion and inappropriate treatment. This re-valuation of the utility of medical data is crucial for bioethicists to explore, especially as medical fields are sorting through increasing amounts of data.